Current cybersecurity threats to patient safety in the operating room: a review - Mohamed Mustaf Ahmed; Omar Kasimieh; Uthman Okikiola Adebayo; Zhinya Kawa Othman; Shuaibu Saidu Musa; Rahmatullah Nazari; Olalekan John Okesanya; Francesco Branda; Jerico Bautista Ogaya; Don Eliseo Lucero-Prisno III (Patient Safety in Surgery, 2026)
Abstract Surgical, anesthetic, and intensive care practices now depend on a large ecosystem of wired and wireless devices, robotic consoles, imaging and laboratory systems, and cloud infrastructure: the Internet of Medical Things and the smart operating room, which extends care beyond the physical theatre to transcontinental telesurgery. Connectivity that is useful in routine care becomes a failure mode during a cyber incident because surgical pathways depend on uninterrupted access to scheduling, imaging, electronic records, and device data. This narrative review sets out the architecture of the surgical Internet of Medical Things and the main threat categories: ransomware, supply chain and firmware compromise, wireless interception, attacks on teleoperated robotic systems, and insider or workforce-related exposure. It then examines documented incidents at the hospital, emergency, and procedural levels, together with the vulnerability profiles of robotic surgical platforms, cardiac implantable electronic devices, infusion systems, and perioperative monitors. Reported harms include cancelled admissions, interrupted cancer surgery and radiotherapy, and worse outcomes after out-of-hospital cardiac arrest, although most of this evidence is healthcare-wide or device-class specific rather than surgery-specific. Although regulatory and governance responses are strengthening, they remain fragmented. The review highlights secure design engineering, human factors, workforce readiness, specialty-specific threat models, and registries as priorities and draws out what each implies for surgeons, anesthetists, device manufacturers, regulators, and hospital leaders.